OPTIMIZING PRODUCTIVE WAQF EMPOWERMENT ON THE DEVELOPMENT OF SUSTAINABLE HALAL TOURISM IN INDONESIA - Nailul Author; Risma Savhira Dwi L; Raditya Sukmana; Muhamad Abduh (Universitas Muhammadiyah Prof Dr Hamka, 2023)
One of the Islamic social financial instruments is waqf, which contributes to the welfare of the community by retaining the principal of waqf and providing the proceeds to people in need. Waqf when integrated with the tourism sector can improve the community's economy and support the creation of Halal tourism destinations. This research aims to explain the contribution of productive waqf to be optimal in the development of sustainable Halal tourism. This research uses descriptive qualitative method. Waqf management is allowed with any mechanism that does not violate Islamic law. The stages of productive waqf management to be more efficient are to design in detail the goals or objectives of the project to be carried out, then realize the project, and conduct regular monitoring so that the project can run sustainably. The integration of productive waqf with the tourism sector is not only to increase the contribution in the economic aspect, but also to educate the public about the ease of waqf. To optimize the integration of productive waqf in Halal tourism, the government and stakeholders must work together, while also continuing to improve the quality of human resources in terms of management so that it becomes sustainable. Then an optimal branding and marketing strategy is carried out.